About mixed problem for degenerate hyperbolic-parabolic equation - Yeldesbaiy, T.Zh.; Tungatarov, A.B.; Tursynbekova, M.U. (Ye.A.Buketov Karaganda State University Publishing house, 2014)
The hyperbolic-parabolic equation in the upper half plane with given boundary and initial conditions is considered. By the method of generalized Fourier transformation the existence and the uniqueness of the solution of the posed mixed problem are proved.
Түрі өзгеретін гиперболалық-параболалық теңдеу үшін аралас есеп туралы
О смешанной задаче для вырождающегося гиперболо-параболического уравнения
Keywords: hyperbolic and parabolic equations; mixed problem; fourier method and transformation